Recent Advances in the Research of the Seismic Response of RC Precast Buildings at the University of Ljubljana - Zoubek, Blaž; Babič, Anže; Dolšek, Matjaž; Fischinger, Matej; Isaković, Tatjana (Frontiers in Built Environment, 2021)
Although in Europe, precast concrete buildings had been built for decades, their seismic response was poorly understood, which is reflected in ambiguous code requirements and conservative design approaches. Therefore, this structural system was the main focus of several European research projects in the past 2 decades. The University of Ljubljana was actively involved in these projects. The key results of the work performed at the University of Ljubljana are presented and discussed in this paper. The main contributions include: a) the development of a new capacity model of beam-column dowel connections, which are one of the critical parts of the RC precast structural system, b) new insight into the cyclic behaviour of fastening systems of concrete cladding panels, and new design procedures for the estimation of strength and displacement capacity of cladding fasteners, c) the development of a methodology for seismic fragility analysis of RC precast buildings, and the fragility curves of precast RC building classes, which can be used for the safety-calibration of the new design procedures of RC precast buildings, and d) the development of a relatively simple and economically attractive back-up (strengthening) system to prevent the falling of panels in case of a strong earthquake.